The Screen Time Dilemma / Muhamad Izzat Rahim - Rahim, Muhamad Izzat (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Too much of something is bod for us. This saying con be applied to our current situation where many of us ore hooked in front of screens for hours every day. In the post, experts warned us that too much screen time could be detrimental to our health and well-being. However, since the Movement Control Order (MCO) started last year, we have spent most of our time in front of screens utilising gadgets such as smartphone, laptop, and tablet. It was reported that the screen time of Malaysians has increased tremendously during the MCO. Although this is an alarming situation, it is unavoidable since many of our daily tasks and chores are done in front of screens nowadays. For instance, workers need to attend meeting, seminar or training via online platforms which require them to sit in front of a screen tor few hours. On the other hand, the young ones are instructed to sit for online classes or complete their homework using electronic gadgets almost every day.